PENGGUNAAN MEDIA TANAM DAN PUPUK ORGANIK CAIR PADA TAHAP AKLIMATISASI TERHADAP PERTUMBUHAN BIBIT ANGGREK BULAN (Phalaenopsis amabilisi) HASIL KULTUR JARINGAN - Rini Suryani; Mya Novita Sari (University of Prof. Dr. Hazairin, SH, 2019)
Tissue culture propagation is mostly done to increase orchid seeds. However, the acclimatization stage in tissue culture is a very important factor because climate conditions in green houses are very different from the conditions in the culture bottle. Besides that the planting medium and fertilizer given at the acclimatization stage need to be considered so that orchid seedlings can grow and develop optimally. This study aims to obtain planting media and obtain good liquid organic fertilizer at the acclimatization stage on the growth of moon orchid seedlings (Phalaenopsis amabilisi) resulting from tissue culture. The completely Randomized design was used with two factors and 3 replications. The first factor was type aclimatization the medium of fern root, rice husk, and coffee compost. The second factor of liquid organic fertilizer. The type is control, SUPRA liquid fertilizer and Bioto Grow. The variables observed were the percentage of life, the increased of the planlet height, the time of shooted, the increased of the number of leaves, the increased of the leaf length, number of leaves, the increased of the stem diameter. Observation data were analyzed using variance analysis and BNT further testing. The results showed that the two types of fertilizer used had no significant effect on plantlets height, when new leaves grew, leaf length, number of leaves, but significantly affected the stem diameter. The three types of growing media have a significant effect on plant height, when growing new leaves, leaf length, number of leaves, and stem diameter. While the interaction in both treatments did not show the real effect on all observed variables. The use of good media is seen in coffee compost and fern root media through the application of Bioto Grow liquid fertilizer.